2019
DOI: 10.1037/str0000091
|View full text |Cite
|
Sign up to set email alerts
|

The associations of quantitative/qualitative job insecurity and well-being: The role of self-esteem.

Abstract: Job insecurity is recognized as one of the most prominent job stressors for employees. Despite decades of research, the concurrent examination of both quantitative (i.e. perceived threat of job loss) and qualitative (i.e., perceived threat of losing some job features) job insecurity and the analysis of their different relationships with well-being at work have received relatively scarce attention. This study examined a moderated mediation model of the relationship between quantitative job insecurity and well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 53 publications
6
50
0
2
Order By: Relevance
“…Available evidence clearly showed that job insecurity has detrimental effects on well-being and health ( De Witte et al, 2016 ), performance ( Cheng and Chan, 2008 ), and job attitudes ( Vander Elst et al, 2014 ). More in detail, several studies ( Sverke et al, 2002 ; Callea et al, 2017 ) reported that job insecurity can negatively affect job satisfaction because, through the anticipation of job loss (thus acting as a powerful stressor), it can decrease the pleasant feelings associated with his/her own job. Based on such evidence, we anticipated that a negative association would have existed between job insecurity and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence clearly showed that job insecurity has detrimental effects on well-being and health ( De Witte et al, 2016 ), performance ( Cheng and Chan, 2008 ), and job attitudes ( Vander Elst et al, 2014 ). More in detail, several studies ( Sverke et al, 2002 ; Callea et al, 2017 ) reported that job insecurity can negatively affect job satisfaction because, through the anticipation of job loss (thus acting as a powerful stressor), it can decrease the pleasant feelings associated with his/her own job. Based on such evidence, we anticipated that a negative association would have existed between job insecurity and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained later by Lim (1996) , and Preuss and Lautsch (2002) . More recently, both Callea et al (2017) and Chirumbolo et al (2017) surveyed different samples of Italian workers finding significant negative effects on job satisfaction, also distinguishing between qualitative and quantitative job insecurity as separate, albeit related, predictors. Thus, we propose that:…”
Section: Job Insecurity and Job Satisfactionmentioning
confidence: 99%
“…Indeed, previous research has demonstrated that qualitative job insecurity is associated with a decline in employee well-being [19,21], organizational commitment [4], career satisfaction [22], and job performance [5,6,23], and an increase in turnover intentions [3] and counterproductive work behavior [7]. Since no prior studies have examined the relationship with informal learning, we aim to examine the negative implications of qualitative job insecurity for employees’ informal workplace learning.…”
Section: Introductionmentioning
confidence: 99%
“…Felt quantitative job insecurity relates to concerns about potential job loss, and felt qualitative job insecurity to concerns about how the job will look like in the future [10,11]. To date, qualitative job insecurity has attracted comparatively little research attention [12], and the combination of felt quantitative and qualitative job insecurity is rarer still (see [13,14] for exceptions). Latent profile analysis is still relatively new in a domain that is dominated by a variable-centered approach (see [15] for exceptions).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence from variable-centered studies suggests a positive correlation between quantitative and qualitative job insecurity. Yet, correlations vary from low (e.g., r = 0.14 in [30]), over medium (e.g., r = 0.26 in [13]) to high (e.g., r = 0.82 in [31]; r = 0.79 in [32]).…”
Section: Introductionmentioning
confidence: 99%